RANCANG BANGUN SISTEM KONTROL PERANGKAT LISTRIK RUMAH TANGGA MENGGUNAKAN TEKNOLOGI INTERNET OF THINGS (IoT) - N, ANDI ROSMAN (SAINFIS: Jurnal Sains Fisika, 2023)
This research aims to control household electrical devices using Internet of things (IoT) technology, where the electrical device will be controlled using a smartphone, making it easier for user when controlling electrical devices. The type of study conducted is research and development (R&D), which develops an electrical device control system using the prototype development method. The results showed that in this system, users could control electrical devices anytime and anywhere without space and time restrictions by using two ways, namely using google assistant voice commands and virtual buttons contained in Blynk applications. Google Assistant voice command mode works based on voice commands inputted through google assistant received by Blynk application, and nodemcu will respond to the management, then the relay will execute orders based on commands inputted through google assistant to turn on and off the power device. Virtual button mode is a mode where we control the electric device using the virtual button in the blynk application, then the nodemcu will respond to the command from blynk, and the relay will execute the order to control the power device.